Interleukin-1 regulates follicular T cells during the germinal center reaction - Belbezier, Aude; Engeroff, Paul; Fourcade, Gwladys; Vantomme, Hélène; Vaineau, Romain; Gouritin, Bruno; Bellier, Bertrand; Brocheriou, Isabelle; Tchitchek, Nicolas; Graff-Dubois, Stephanie; Klatzmann, David (Frontiers in Immunology, 2024)
To study the role of IL-1 receptors in the regulation of the B cell response by T follicular helper (Tfh) and T follicular regulatory (Tfr) cells, we generated mice with IL-1 receptors inactivated in these cells and measured antibody production and cell activation upon immunization. While IL-1β concentration is increased in the draining lymph node after immunization, antigenspecific antibody levels and cell phenotypes indicated that IL-1β can activate both Tfh and Tfr cells through IL-1R1 stimulation. Surprisingly, IL-1R2 and IL-1Ra expression on Tfr cells does not block IL-1 activation of Tfh cells, but rather prevents IL-1/IL-1R1-mediated early activation of Tfr cells. IL-1Rs similarly regulate antibody response against autoantigens and its related pathophysiology in an experimental lupus model. Altogether, these results show that IL-1 inhibitory receptors expressed by Tfr cells prevent their own activation and suppressive function, thus licensing IL-1-mediated activation of Tfh cells after immunization.